RESPONSE OF RICE CROP (SUPER BASMATI) TO DIFFERENT NITROGEN LEVELS. - Z. Manzoor; T. H. Awan; M. A Zahid; F. A. Faiz (Journal of Animal and Plant Sciences, 2006)
Field experiment was conducted during the kharif seasons of three successive years from 2000 to 2002 at Rice Research Institute, Kala Shah Kaku, Lahore, Pakistan to find out the most appropriate level of nitrogen to get maximum paddy yield of rice variety, Super Basmati. Effect of nine different nitrogen levels i.e. 0, 50, 75,100,125,150,175,200 and 225 kg/ha on paddy yield and yield components were studied in this experiment. Plant height, number of productive tillers per hill, panicle length, number of grains per panicle, 1000 grain weight and paddy yield showed increasing trend from 0 kg N/ha up to 175 kg N/ha. The yield parameters including paddy yield, number of grains per panicle and 1000 grain weight started declining at 200 kg N/ha level and above . Maximum paddy yield (4.24 t/ha) was obtained from 175 kg/ha nitrogen application treatment which also produced highest values of number of grains per panicle (130.2) along with a maximum 1000 grain weight (22.92 gm). The plant height (139.8 cm) along with number of productive tillers per hill (23.42) and panicle length (29.75 cm) was maximum at 225 kg N/ha level.
Keywords: nitrogen levels; parameters; paddy yield; plant height